Respuestas
Respuesta dada por:
1
a)
b)
Respuesta dada por:
0
Primero convertir Todo al
mismo denominador
2.4/3x4 + -5x2/6x2 + _7/12=
8/4- 10/12 - 7/12= -9/12=-3/4
7/4 - 1/5 + 2/3 vamos à convertir todo al
mismo denominador
7x15/4x15 - 1x12/5x12 + 2x20/3x20=
105/60 -12/60+40/60= 133/60
mismo denominador
2.4/3x4 + -5x2/6x2 + _7/12=
8/4- 10/12 - 7/12= -9/12=-3/4
7/4 - 1/5 + 2/3 vamos à convertir todo al
mismo denominador
7x15/4x15 - 1x12/5x12 + 2x20/3x20=
105/60 -12/60+40/60= 133/60
Preguntas similares
hace 3 años
hace 3 años
hace 3 años
hace 6 años
hace 6 años
hace 6 años
hace 8 años